Human Resources and the Growth of Islamic Banks in the Disuptive Era (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Some of the human resources which working in the Islamic banks are threatened with being replaced by machines or digital banking system. One of its is that the position of teller serving cash deposit and withdrawal transactions has been replaced by an automated teller machine (ATM). This one of the impacts of the disruption era that occurred due to the implementation of the digital era 4.0. This study is porpose to analyze how the growth of the human resources number and profites obtained by Islamic banks in the disruption era. This study used a qualitative methode with a descriptive analysis approach. Primary data was obtained through in- depth interviews with various types of Islamic banks regarding constraints and strategies for increasing the growth of Islamic banks in the disruptive era. Secondary data was obtained through www.ojk.go.id in the menu of Islamic banking statistics, especially the number of workers and profits of Islamic banks in Indonesia during the disruption era. This research show the result that the growth in the number of Islamic bank human resources in the disruptive era experienced the most decline in July 2021 with a total of 6,769 people or 10.63%. However, the average growth in the number of Islamic bank human resources always increases by 54 people every year or 0.13%. Meanwhile, the profit growth for Islamic banks in Indonesia from 2020 to 2023 tends to decrease. The average profit growth of Islamic banks in the disruptive era experienced a decrease of 1.19% for each period. This research shows that Islamic banks are more focused on strategies in overcoming disruptive eras by making major changes from the technological aspect in the hope of reducing human resources. However, this resulted in an increase in operational costs of Islamic banks.